Women political empowerment : political parties as agent of political socialization in empowering women political participation - Megat Muhammad Syamil Megat Sharif (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The representation of women in Malaysia is still considered as under-represented as it does not meet the agreed 30% stated in the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) that was signed by the government in 1995. The failure to ensure the minimum 30% in decision-making groups resulted in men overshadowing the women in such circumstances. This study aims to look at the pattern of women’s political participation within the time frame of 2013 until 2020. Women’s political participation in the context of this study will be focusing on women candidacy in parliamentary and state assembly seats in the 13th and 14th General Elections. In addition, this study looks into the appointment of women as Ministers and Deputy Ministers after their success in securing seats in both General Elections. This study also looks at the pattern of women who contested for top positions at the party level during their party’s election. Political participation also refers to the opportunity provided by the political parties in both written constitution and also common practices adopted by political parties in Malaysia. Moreover, this study also analyses the challenges faced by women politician. To answer the problem that has been highlighted, this study has managed to interview several of the prominent women politician and also top leadership figures from UMNO, PKR, DAP, WARISAN, AMANAH, MCA and GERAKAN political parties. This study also explores the political parties’ constitutions in order to understand the roles and the opportunities given to their women members. The results of the study shows that opposition parties are bolder in fielding more women candidates in the 13th and 14th General Elections. Moreover, this study also sees that all political parties have no objection in accepting and welcoming women to join as their members. However, there are several challenges that have been identified in this study that have restricted women from being actively involved in politics, which are institutional challenges and personal challenges.